PELATIHAN EMPATI UNTUK MENURUNKAN PERILAKU BULLYING PADA PELAKU BULLYING DI SEKOLAH DASAR - Lailatul Izzah; Sukarti Sukarti; Uly Gusniarti (Universitas Islam Indonesia, 2019)
This study aims to determine the effect of empathy training to reduce bullying behavior on the offender bullying in primary school. Subjects in this study were 10-11 years old who have low and medium empathy scores nor high and medium bullying behavior. There were eight students who become participants in this study. The data were collected by using interview, observation, peer relations questionaires, bullying scales, and empathy scales. This study was using one group pretest-posttest design. The data were analyzed by using quantitative analysis of two related sample test by Wilcoxon. The results showed that empathy scores (Z=-2.52, p=0.012 (p<0.05)) and bullying scores (Z=-2.207, p=0.027 (p<0.05)) underwent a significant change pretest-posttest. Meanwhile, empathy scores Z=-1.452, p=0.146 (p>0.05)) and bullying scores (Z=-1.897, p=0.058 (p>0.05)) had no significant changes posttest- follow up. Furthermore, empathy scores (Z=-2.530, p=0.011 (p<0.05)) and bullying scores (Z=-2.533, p=0.011 (p<0.05)) underwent a significant change pretest- follow-up.